Extreme airborne asbestos concentrations in a public building. Issue 7 (July 1992) - Ganor, E; Fischbein, A; Brenner, S; Froom, P
Abstract : Fibre concentrations of asbestos were measured in the air of a communal dining room in which the damaged ceiling had a sprayed on coating of insulation containing asbestos. The average concentration of crocidolite asbestos fibres was 4 f/cm3, 20 times the highest air concentration that appears to have been reported previously for a public building. It is concluded that although air concentrations of asbestos fibres in public buildings containing asbestos insulation materials are usually low, high concentrations can occur. This may have implications for the risk of exposed persons developing diseases associated with asbestos.